Advertising regulations in pharmaceutical markets: Product versus enlightenment - Junichiro Ishida; Tsuyoshi Takahara (Osaka University, Institute of Social and Economic Research (ISER), 2019)
This paper analyzes the optimal content regulation of direct-to-consumer advertisement (DTCA) in a pharmaceutical market, with particular focus on the distinction between product and enlightenment advertisement. Firms are allowed to freely promote their own specific products under product DTCA, whereas they can only advertise the presence of a disease and its typical subjective symptoms under enlightenment DTCA. The content regulation changes the nature of market competition and the incentive to invest in advertisement, thereby yielding substantial welfare and policy implications. The overall welfare impact of the content regulation is ambiguous and depends, among other things, on the cost effectiveness of advertisement and the market-size distortion induced by product DTCA. We also analyze the effect of free market pricing and argue that a less stringent advertisement regulation, i.e., product DTCA, is often complementary to a less stringent price regulation.
Keywords: M37; I11; I18; 330; DTCA; Advertisement content regulation; Prescription decision